Grassroots Politics and Oil Culture in Venezuela : The Revolutionary Petro-State - Strønen, Iselin Åsedotter (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is published open access under a CC BY 4.0 license. This book presents an ethnographic study of how grassroots activism in Venezuela during the Chávez presidency can be understood in relation to the country's history as a petro-state. Taking the contested relationship between the popular sectors and the Venezuelan state as a point of departure, Iselin Åsedotter Strønen explores how notions such as class, race, state, bureaucracy, popular politics, capitalism, neoliberalism, consumption, oil wealth, and corruption gained salience in the Bolivarian process. A central argument is that the Bolivarian process was an attempt to challenge the practices, ideas, and values inherited from Venezuela's historical development as an oil-producing state. Drawing on rich ethnographic material from Caracas' shantytowns, state institutions, as well as everyday life and public culture, Strønen explores the complexities and challenges in fostering deep social and political change.
Keywords: Social sciences.; Area studies.; Environmental sociology.; Political sociology.; elektronické knihy; electronic books